MANAGEMENT OF LABORATORY SCHOOLS BY THE STATE UNIVERSITY OF THE FORMER EDUCATIONAL PERSONNEL EDUCATION INSTITUTE (LPTK / IKIP) (Studies in Legal Perspective) - Endang Endang (Universitas Padjadjaran, 2021)
The aim of this research is to look into the legal perspective on laboratory management by the State University in Indonesia, the former The Educational Personnel Education Institute (LPTK / IKIP). The site that becomes the object of this study is “Universitas Pendidikan Indonesia” (UPI, Bandung) which organizes a Laboratory School in the form of a formal school which includes primary and secondary education. UPI laboratory school strives to provide educational services to students according to their expectations (vision and mission of the laboratory school), becoming a forum for the development of various professional teachers and educational practices. In addition, schools can also become models for creative and innovative learning practices by professional teacher candidates in collaboration with the relevant LPTK (Educational Institutions) and Provincial, Regency / City Education Offices. The results of the study concluded that the authority to manage formal education units - at the levels of PAUD / TK, SD, SMP, and SMA, rests with the regency / city government and the provincial government or the community as the organizing institution, not the authority of higher education. If the UPI Laboratory School is a formal school, then UPI must establish an organizing legal entity.